Role of medical Thoracoscopy in the Management of Multiloculated Empyema - Kamran Khan Sumalani (BMC Pulmonary Medicine, 2018)
Abstract Background The treatment of early pleural empyema depends on the treatment of ongoing infection by antimicrobial therapy along with thoracocentesis. In complicated empyema this treatment does not work and lung will not expand until removal of adhesions. The objective of the current study is to analyze the experience of management of multiloculated, exudative and fibrinopurulent empyema through rigid medical thoracoscopy under local anaesthesia and to explore new ways to manage the entity. Methods This is a descriptive case series in which 160 patients were recruited through non-probability convenient sampling, from department of pulmonology, Jinnah postgraduate medical centre, Karachi, from September 2014 to August 2016. All patients underwent medical thoracoscopy under local anesthesia. Written Informed consent was taken from the study participants. Ethical approval was obtained from Ethical Review Committee of the hospital. Patients age > 70 years, those with multiple organ failure and bleeding disorders were excluded. Results Out of 160 patients, 108 (67.50%) were male and 52 (32.5%) were female with mean age 25.37 years (range 16 to 70 years). Out of total, 102 (63.7%) had tuberculous empyema, while pleural biopsy of 58 (36.3%) patients was suggestive of non-tuberculous empyema. Final evolution through chest x-ray revealed complete resolution in 92 (57.5%), partial resolution in 58 (36.25%) patients. 9 (5.6%) developed persistent air leak while 1 (0.6%) patient expired due to urosepsis. Conclusion Medical Thoracoscopy under local anesthesia is a safe, efficient and cost effective intervention for management of complicated empyema, particularly in resource constraint settings.